CTD variables from cruises conducted offshore of Ensenada, Baja California, Mexico (IMECOCAL sampling Line 100) from 1998 to 2016 - José Martín Hernández-Ayón; Norma Lidia Oliva-Mendez; José Augusto Valencia-Gasti (PANGAEA, 2025)
The dataset includes temperature and salinity CTD profiles performed at 8 hydrographic stations conducted offshore of Ensenada, Baja California (Mexico) along Line 100 of the Investigaciones Mexicanas de la Corriente de California (IMECOCAL) program. The regular IMECOCAL stations of Line 100 are spaced 37 km apart and extend a maximum distance of 220 km offshore. The stations were performed on board the Francisco de Ulloa (1998 to 2013), BIPO (2014-2015), and Alpha Helix (2016) research vessels. CTD casts were performed down to 1000 m depth (bottom depth allowing) by means of a 24 Hz sampling rate mainly with a SeaBird CTD system equipped with factory-calibrated primary and secondary sensors for temperature and conductivity. Data were processed using the UNESCO 1980 equation of state, and both measured and derived quantities were averaged over 1 dbar intervals using software provided by the manufacturer. Data columns include sampling date/time stamps in ISO format, longitude, latitude, depth, pressure, temperature, salinity, and potential density anomaly information. The CTD data were used to estimate pH, calcium carbonate saturation states, and DIC concentrations from 1998 to 2016 based on the algorithms of Alin et al. (2012).